PENCABUTAN HAK UNTUK MEMILIH DAN DIPILIH BAGI TERPIDANA TINDAK PIDANA KORUPSI - Ardiansyah, Denny (Jurnal Cakrawala Hukum, 2017)
The criminal act of corruption is a criminal act that has a tremendous impact on the stability of the nation and state. The impact of this criminal offense is highly systemic and incurs enormous losses in the state financial sector. some cases occurred an ex-convict corruption case, when it was out of running his penalty, it turns out to be more officials in the environment of his service. The purpose of this study is first to examine or analyze the formulation policy of revocation of the Right to be elected and vote for convicted corruption, both reviewing or analyzing the policies that can be applied in the formulation in the future. The research method used in this legal research is juridical-normative. Whereas in essence the regulation concerning additional crime shall be the revocation of certain rights including the right to be elected and to vote already regulated by the laws and regulations in Indonesia. Although there has been renewal in the draft law the additional criminal provisions may stand on its own, but the right to vote and vote is unclear, so there is still a gap for corrupt criminals who can be public officials again. DOI: https://doi.org/10.26905/idjch.v8i2.1802